Pamphilius japonicus feeds on Cornus: the first Old World record of Pamphiliidae (Hymenoptera) associated with Cornaceae - Shinohara, Akihiko; Ibuki, Shin-Ichi; Kakuda, Tsuneo; Kameda, Yuichi (Zootaxa, 2019)
We identified newly discovered pamphiliid larvae feeding on Cornus in Tochigi and Ibaraki Prefectures, Honshu, Japan, with Pamphilius japonicus Shinohara, 1985, by molecular methods using mitochondrial cytochrome oxidase subunit 1 (COI) gene sequences. The host plant of P. japonicus was unknown. This is the first record of the Cornaceae as a host plant of the Pamphiliidae in the Old World. The larvae were solitary leaf-rollers on Cornus and discovered mainly on small young trees in shadowy forests.